Hybrid Legal Intelligent System Using Fuzzy and Neural Networks - Sridevi, S; Venkata Subba Reddy, P (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we describe the implementation of Hybrid Intelligence system for Indian legal domain by using neural network and fuzzy technique. The objective of this research is to develop a legal expert system for auto-insurance, a domain within the Indian legal system. We have proposed legal reasoning system which basically integrates rule based and case based reasoning in a structured manner for critical task units in auto-insurance domain. The end user of the system can be the insurer as well as lawyer in order to take any legal actions. The system mainly handles three main functional blocks of auto-insurance claim processing: i) validation of rules and regulations of motor vehicle act, ii) verification of the ‘extent of damage’ attribute, and iii) analysing history legal cases for reference. The scope of this hybrid system is limited to validation and verification of auto-insurance claim processing pertaining to Indian legal system. All these functional blocks play important role in providing logical solution for claim compensation.